2018
DOI: 10.1111/acv.12466
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding causes decreased seminal quality affecting pregnancy and litter size in the endangered black‐footed ferret

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 46 publications
(51 reference statements)
0
33
0
Order By: Relevance
“…Furthermore, catheterization was not repeated if an adequate number of sperm were observed, possibly resulting in incomplete collection of all available sperm in the urethra. Reports describing sperm morphology and incidence of abnormalities vary greatly in this species, and appear to be impacted by age ( Wolf et al ., 2000 ) and level of inbreeding ( Santymire et al ., 2018 ). Sperm morphology following UC was similar to that described previously (0–89%, μ = 33 ± 1.1; Santymire et al ., 2018 ) with the predominant abnormalities including damaged acrosomes, coiled tails and bent tails or midpieces.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, catheterization was not repeated if an adequate number of sperm were observed, possibly resulting in incomplete collection of all available sperm in the urethra. Reports describing sperm morphology and incidence of abnormalities vary greatly in this species, and appear to be impacted by age ( Wolf et al ., 2000 ) and level of inbreeding ( Santymire et al ., 2018 ). Sperm morphology following UC was similar to that described previously (0–89%, μ = 33 ± 1.1; Santymire et al ., 2018 ) with the predominant abnormalities including damaged acrosomes, coiled tails and bent tails or midpieces.…”
Section: Discussionmentioning
confidence: 99%
“…Santymire et al. (2019) found that inbreeding mainly affects the percentages of motile sperm, progressive motile sperm and in the presence of abnormal forms. We do not have genetic data, but consanguinity cannot be entirely excluded because the animals come from the same commercial breeder.…”
Section: Discussionmentioning
confidence: 99%
“…The idea for creating sustainable insurance populations for rare species was pioneered nearly 40 years ago by zoos (Conway 1980). In this “ark” paradigm, certain species are intensively managed by cooperating institutions that share individuals (figure 1), or occasionally germplasm (Santymire et al 2018), in a “metapopulation” (Long et al 2011). A pedigree is maintained and relatedness among animals (mean kinship) used to determine best matings to retain gene diversity (Ballou and Lacy 1995).…”
Section: Ex Situ Programs and Zoosmentioning
confidence: 99%
“…After reaching maximal abundance within 25 years, population abundance began to decline because of the (1) negative impact of random variation in reproductive success and survival across years, and (2) gradual accumulation in inbreeding that occurs in persistently small populations. Genetic impacts can occur even in zoo populations that are properly managed by mean kinship-based metrics (e.g., Santymire et al 2018). In contrast, the SPA population continued to grow ∼6% annually for almost 40 years before slowing (figure 8).…”
Section: Simulation Modeling To Demonstrate Value Of Herd Managementmentioning
confidence: 99%